Brain Natriuretic Peptide in Patients with Acromegaly: A Comparative Study between those with and without Obstructive Sleep Apnea - Shaymaa Dheyab Hammood; Eham Amer Ali; Abbas Mahdi Rahmah (Wolters Kluwer Medknow Publications, 2024)
Background: Acromegaly is a rare endocrine disorder; it has an incidence of 4 per million annually and a prevalence of 40 per million. It is due to growth hormone-secreting pituitary adenoma. The objective of our study is to evaluate the levels of brain natriuretic peptide (BNP) in patients with acromegaly with and without obstructive sleep apnea (OSA). Materials and Methods: One hundred five registered patients with acromegaly in the National Diabetes Center-Mustansiriyah University were enrolled in the study. Out of 105 patients with acromegaly, 81 have OSA while the remaining 24 have no OSA. OSA affects 81.8% of males and 72% of females. All recruited patients have given oral consent to participate in the study which was conducted during the period from January to October 2023. Results: Males with OSA had a mean age of 52 years while those without OSA had a mean age of 46 years. Epworth Sleepiness Scale is higher among those with OSA. BNP is found to be higher in females with OSA (905.54 pg/ml) while in males with OSA, it drops down to 878.76 pg/ml. In no OSA group, the BNP level was 355.33 ± 30.1 pg/ml while in those with OSA, it jumped to 890.66 ± 205.63 pg/ml. Conclusions: The results showed that BNP was elevated in patients with acromegaly and OSA versus those without OSA, OSA is more common in males particularly when they get older.